Effect of a plant vitamin on the growth of the tomato plant (Lycopersicon esculentum) - Perera, N.; Sirimanne, C.; Hettiarachchi, C. (University of Colombo, 2011)
Abstract The research was carried out to study the effect of a plant vitamin on growth of the tomato plant and the resultant residue levels in the tomato fruit. The field experiment was designed according to the Randomized Complete Block Design (RCBD). Several growth parameters were monitored to determine the growth rate of tomato plants. The macro, micro and trace element contents were determined after the fruits were harvested. The statistical analysis was carried out to analyze the results. Analysis of the growth parameters indicates that the plant vitamin does not help to increase the growth rate in tomato plant and in the tomato fruit. Results also reveal an increase in N, P, Ca and Zn levels in the tomato fruits